Evaluation of Histopathological Features and Some Immunological Markers in Diabetic Foot Ulcer Patients: Evaluasi Gambaran Histopatologi dan Beberapa Penanda Imunologi pada Pasien Ulkus Kaki Diabetes - Faisal, Ahmed Nassir; Abbas, Abbas Muhsin (Indonesian Journal on Health Science and Medicine, 2024)
Background; diabetic foot patients are affected by complications with any injury, more than healthy people, as a result of the delay in discovering the problem, as the patient’s lack of awareness of repeated injuries leads to complications with difficulty in treatment, these disorders are related to controlling the level of sugar in the blood. 39 samples of diabetic foot patients were collected from Al-Rifai General Hospital and the Diabetes Center in Nasiriyah city to conduct histological examinations. Aims of the study; the current study aims to characterize the histopathological features of diabetic foot ulcer cases. And assess immune and biochemical parameters associated with diabetic foot ulcer. In addition to evaluate the correlation between histopathological changes and immune responses. Methodology; Samples (blood, tissue specimen) were collected from diabetic patients with diabetic foot ulcer from Al-Rifai General Hospital and the Diabetic Center in in Nasiriyah city from April 2022 to september2022. Histopathological sections were prepared according to (Bancroft and Steven, 2008) , cytokines (TGF- β, IFN- γ and IL-17A) measured using the enzyme-linked immunosorbent technique ELISA. Result; the current study aims to demonstrate the histopathological changes associated with diabetic foot. results show purulent ulcer with a large gap between the edges of the lesion necrotic foci in the dermis tissue, Fibrin deposition with focal melanin pigmentation, degenerative changes with compaction of nuclei and extensive granulation formation in the dermis with inflammatory activity. The results showed a significant increase in the concentration of some cytokines (TGF- β, IFN- γ and IL-17A) and some Biochemical parameters such as (HbA1C and Triglycerides) in patients with diabetic foot compared to the healthy group. Conclusions; The present study concluded that the severity of diabetic foot ulcers is closely related to the high level of cytokines in diabetic patients with a preponderance in type 1 diabetes Highlights: tudy examines histopathological changes in diabetic foot ulcer patients. Findings show necrosis, inflammation, elevated cytokines (TGF-β, IFN-γ, IL-17A). Diabetic foot severity linked to cytokines and biochemical imbalances. Keywords: Diabetic foot, gangrene, ulcer, TGF- β, IFN- γ and IL-17A